2014
DOI: 10.1542/peds.2013-3995
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Symptoms in Autism Spectrum Disorder: A Meta-analysis

Abstract: BACKGROUND:In pediatric settings, parents often raise concerns about possible gastrointestinal (GI) symptoms in autism spectrum disorder (ASD), yet the specificity of these concerns are not well studied. OBJECTIVE:To conduct a meta-analysis of research investigating GI symptoms among children with ASD. METHODS:We searched Medline, PsycINFO, and PubMed databases in peer-reviewed journals. Analysis involved studies with a comparison group presenting quantitative data on GI symptoms using combinations of terms f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
443
1
26

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 659 publications
(485 citation statements)
references
References 57 publications
15
443
1
26
Order By: Relevance
“…144 A few small clinical trials have shown beneficial effects for gluten free and casein free diets on symptoms of children with ASD 145,146 that could potentially be attributed to the change in gut microbiota. 4,8,19,61,128,147 Furthermore, in children with autism, the frequency of GI symptoms is increased 148,149 and has been attributed to a low-grade chronic inflammation in the GI tract caused by altered gut microbiota. In a clinical study, oral vancomycin was used as a minimally absorbed antibiotic to treat the GI problems, based on this theory.…”
Section: Emerging Areasmentioning
confidence: 99%
“…144 A few small clinical trials have shown beneficial effects for gluten free and casein free diets on symptoms of children with ASD 145,146 that could potentially be attributed to the change in gut microbiota. 4,8,19,61,128,147 Furthermore, in children with autism, the frequency of GI symptoms is increased 148,149 and has been attributed to a low-grade chronic inflammation in the GI tract caused by altered gut microbiota. In a clinical study, oral vancomycin was used as a minimally absorbed antibiotic to treat the GI problems, based on this theory.…”
Section: Emerging Areasmentioning
confidence: 99%
“…Finally, neuroinflammation is also a frequent finding in postmortem brains of autistic individuals [64,65]. It may represent a nonspecific consequence of insufficient neurite pruning and abnormal wiring of neural networks, resulting in elevated oxidative stress (possibly a common feature shared by several neurodevelopmental disorders) [66], but it could also stem from a broader immune dysfunction which, together with gastrointestinal disturbances and recurrent infections, collectively qualifies ASD as a systemic disorder [67][68][69][70][71].…”
Section: Autism Spectrum Disorder: Clinical Traits Neuropsychologicamentioning
confidence: 99%
“…Here we illustrate use of the method for a study of colonic motility in the NL3 R451C mouse model of autism, which expresses a missense mutation in the Nlgn3 gene encoding the synaptic adhesion protein Neuroligin-3 16 . This mutation was first identified in patients diagnosed with Autism spectrum disorder (ASD) 17 , which is strongly associated with GI dysfunction [18][19][20][21][22] . We investigated whether the NL3 R451C synaptic mutation affects neural outputs in the ENS using the video imaging technique.…”
Section: Introductionmentioning
confidence: 99%